Effectiveness of disinfectant solutions associated or not with brushing on the biofilm control of a 3D printed-denture base resin - Thaís Soares Bezerra Santos NUNES; Marcela Dantas Dias da SILVA; Sabrina Romão Gonçalves COELHO; Hamile Emanuella do Carmo VIOTTO; Ana Carolina PERO (University of São Paulo, 2023)
Abstract The formation of biofilm on denture bases is a recurrent clinical problem that favors the development of denture stomatitis. The effectiveness of a hygiene protocol in a 3D-printed denture base resin is still uncertain. Objective To evaluate of the effectiveness of immersion, associated or not with brushing in a soap solution, on the biofilm control of a 3D-printed denture base resin. Methodology Specimens of denture base resins [Cosmos Denture (COS) and Classico (CLA/control)] were contaminated in vitro with Candida albicans and immersed in sodium hypochlorite 0.25% (SH, alkaline peroxide) AP, chlorhexidine digluconate 2% (CD or PBS-Control), associated or not with brushing with 0.78% Lifebuoy soap. Roughness was evaluated before and after brushing and immersion. The effectiveness of the protocols was assessed by CFU/mL, cellular metabolism (XTT), scanning electron microscopy (SEM), and confocal scanning laser microscopy. Data were analyzed by T student, ANOVA/Welch, and Tukey/Gomes-Howell pos-hoc tests (α = 0.05). Results CLA showed greater roughness than COS. CFU/mL and XTT were higher in COS resin with a higher hyphae formation. Immersion in SH and CD eliminated CFU/mL and reduced XTT for both resins, associated or not with brushing. AP reduced CFU/mL only when associated with brushing. Conclusions The biofilm on the 3D-printed resin was thicker and presumably more pathogenic, regardless of its smoother surface. Immersions in SH 0.25% and CD 2% are effective hygiene protocols for both resins, associated or not with brushing. AP should be recommended when associated with brushing with a Lifebuoy 0.78% solution.